New Board Members: Meet the Fresh Faces at ChemPlusChem. Issue 6 (9th May 2016) - Spiniello, Marisa
Abstract : Get on board ! The first four years of ChemPlusChem concluded and the initial term for several board members is at an end. Here we introduce new members of the editorial and international advisory boards to our readers.